92 CONTINUING TO 'BE HIP': ORTHOGERIATRIC SERVICE IMPROVEMENTS IN 2021. (25th October 2022) - Thomas, N; Stankard, A; Cosgrave, N; Conlon, B; Monahan, P; Halpin, T; Britton, D; Byrne, P; McShane, S; Sohail, I; Grogan, AM; Reilly, A; et al.
Abstract: Background: Scotland first demonstrated that adherence to nationally agreed hip fracture standards improve patient survival, reduces the duration of admission, and reduces the need for high dependency care. Our study aims to assess adherence to the Irish Hip Fracture Standards (IHFS) in our hospital for 2021 amidst the COVID-19 pandemic, translating to improved clinical outcomes for our patients. Methods: The IHF database was retrospectively analysed, comparing quarters 1-4 in 2021 with our 2020 results. Results: IHFS1, patient time to the ward < 4hours, was maintained at 67% in 2021 versus 71% overall in 2020. There was improvement in IHFS2, time to surgery within 48 hours, up to 73% in 2021 versus 66% in 2020. IHFS3 was 4% in 2021 versus 3% overall in 2020. Further improvements were noted for IHFS4, with 95% of patients reviewed by a Geriatrician in 2021 versus 87% in 2020. IHFS5 also improved with 97% of patients receiving a bone health assessment in 2021 versus 87% in 2020. Moreover, IHFS6, improved with 97% of patients undergoing a specialised falls assessment in 2021 versus 87% in 2020. Conclusion: The improvement in 2021 figures is reflective of the return of redeployed services during the COVID-19 pandemic inclusive of the Orthogeriatric Service, the Fracture Liaison Service Advanced Nurse Practitioner, the Trauma Co-ordinator, and the specialist Orthopaedic ward complete with its Orthopaedic nurses and Multi-Disciplinary Team, and improved Emergency Department pathways. These continued improvements in the IHFS further emphasise that success is dependent on a team that is joined at the hip